A review of Gabonese gorillas and their pathogens: Diversity, transfer and One Health approach to avoid future outbreaks? - Boundenga, Larson; Makouloutou-Nzassi, Patrice; Ngoubangoye, Barthelemy (Frontiers in Parasitology, 2023)
In Africa, great apes, particularly gorillas, are considered to be the reservoir of several infectious agents with zoonotic potential. However, data on the pathogens harbored by some primate species are still scattered in different popularization documents. Thus, it seemed interesting to us to make a synthesis of the available data on pathogens (parasites, bacteria and viruses) identified in gorillas living in different ecosystems of Gabon in Central Africa. Thus, this review article presents the diversity of pathogens identified in gorillas in Gabon, the impact of these infectious agents on the health of primates, the cases of transfer between gorillas and humans and the interest of a One Heath approach for a better understanding of the ecology of diseases infection in Gabon.